The Works of John Ruskin, Volume 21, The Ruskin Art Collection at Oxford - Ruskin, John 1819-1900 (Cambridge University Press, 1906)
The influence of John Ruskin (1819–1900), both on his own time and on artistic and social developments in the twentieth century, cannot be over-stated. He changed Victorian perceptions of art, and was the main influence behind 'Gothic revival' architecture. As a social critic, he argued for the improvement of the condition of the poor, and against the increasing mechanisation of work in factories, which he believed was dull and soul-destroying. The thirty-nine volumes of the Library Edition of his works, published between 1903 and 1912, are themselves a remarkable achievement, in which his books and essays - almost all highly illustrated - are given a biographical and critical context in extended introductory essays and in the 'Minor Ruskiniana' - extracts from letters, articles and reminiscences both by and about Ruskin. This twenty-first volume contains the catalogues of the Ruskin Art Collection at Oxford
Title from publisher's bibliographic system (viewed on 05 Oct 2015)